"Through the looking glass: envisioning new library technologies" Drones. Issue 7 (5th September 2016) - Fernandez, Peter
Abstract : Purpose: The word "drone" is the common term for an unmanned aerial vehicle – a robot that combines flight with sensors (usually cameras) to allow for unprecedented freedom in observing and interacting with the world. Design/methodology/approach: This column will explore the technology that makes modern drones possible, what makes drones useful and the role of libraries in making drones accessible to their patrons, now and in the future. Findings: Many of these applications are equally appealing to hobbyists and professionals. For some small-scale gardeners, drones can be used to scare away pests, such as deer, or take aerial photographs that provide a new perspective of their garden. Originality/value: For the agriculture industry, drones already account for $864.4 million in spending per year and are expected to grow to account for over $4 billion by 2022, as they are used not only to monitor and plan crops but also to plant seeds and provide accurate pesticide control (Wood, 2016 ).